2023
DOI: 10.2459/jcm.0000000000001433
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography and nuclear medicine for the assessment of coronary inflammation: clinical applications and perspectives

Abstract: There is increasing evidence that in patients with atherosclerotic cardiovascular disease (ASCVD) under optimal medical therapy, a persisting dysregulation of the lipid and glucose metabolism, associated with adipose tissue dysfunction and inflammation, predicts a substantial residual risk of disease progression and cardiovascular events. Despite the inflammatory nature of ASCVD, circulating biomarkers such as high-sensitivity C-reactive protein and interleukins may lack specificity for vascular inflammation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…Previous studies have confirmed that FAI reflects peri-coronary inflammation and is associated with vulnerable plaques and inflammatory activities ( 1 , 17 ). Moreover, the paracrine-mediated regulation of vascular homeostasis by PCAT has been reported in a study ( 18 ). In cases of CAD or microvascular dysfunction, radical oxygen species generated in response to regional ischemia can trigger the activation of EAT-driven inflammatory signals by releasing chemokines and inflammatory cytokines, which exert local effects on the underlying coronaries and myocardium ( 18 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies have confirmed that FAI reflects peri-coronary inflammation and is associated with vulnerable plaques and inflammatory activities ( 1 , 17 ). Moreover, the paracrine-mediated regulation of vascular homeostasis by PCAT has been reported in a study ( 18 ). In cases of CAD or microvascular dysfunction, radical oxygen species generated in response to regional ischemia can trigger the activation of EAT-driven inflammatory signals by releasing chemokines and inflammatory cytokines, which exert local effects on the underlying coronaries and myocardium ( 18 ).…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, the paracrine-mediated regulation of vascular homeostasis by PCAT has been reported in a study (18). In cases of CAD or microvascular dysfunction, radical oxygen species generated in response to regional ischemia can trigger the activation of EAT-driven inflammatory signals by releasing chemokines and inflammatory cytokines, which exert local effects on the underlying coronaries and myocardium (18). The possible mechanism is that coronary artery inflammation in patients with impaired coronary blood flow may disrupt the role of PCAT in regulating vascular tension caused by focal inflammation.…”
Section: Discussionmentioning
confidence: 88%
“…Higher CT attenuation in EAT indicates the presence of enlarged adipocytes and infiltration of pro-inflammatory M1 macrophages, indicating inflammation [46,52]. CT attenuation of the surrounding PCAT has prognostic significance in CAD, as elevated attenuation is associated with reduced coronary flow reserve [18,19,53], while a pericoronary fat attenuation index (pFAI) exceeding a specific threshold has been predictive of both all-cause and cardiac mortality [54]. Utilizing the pFAI could potentially improve risk assessment and guide targeted prevention strategies for individuals at higher risk [52].…”
Section: Correlation Between Eat Coronary Inflammation Coronary Flow ...mentioning
confidence: 99%